A flexible and highly sensitive nitrite sensor enabled by interconnected 3D porous polyaniline/carbon nanotube conductive hydrogels. Issue 5 (21st January 2020) - Gao, Fengxian; Teng, He; Song, Jingyao; Xu, Guiyun; Luo, Xiliang
Abstract : A flexible and highly sensitive nitrite sensor based on PANI–CNT hydrogels. Abstract : Conducting polymer hydrogels with superior electrical responsiveness, adjustable chemical properties, and high electrical conductivity are highly desired for electrode materials in assembling flexible and wearable sensors. Herein, we have synthesized PANI–CNT composite hydrogels via a self-assembly strategy for nitrite detection. High-density CNTs are tightly adsorbed onto PANI hydrogels with a 3D porous hierarchical microstructure via π–π interactions to form PANI–CNT hydrogels. The 3D porous network of PANI hydrogels and the high conductivity of CNTs largely benefit electrolyte ion diffusion and transfer. The hydrophilic nature of PANI–CNT hydrogels provides an outstanding interface between electrolytes and electrodes. The PANI–CNT hydrogel-modified electrode shows high sensitivity (271.48 μA mM −1 cm −2 ), with an average response time of 3 s, a linear range from 20 μM to 1.8 mM, and a low detection limit of 7.8 μM. Moreover, a flexible electrochemical sensor for nitrite detection was successfully prepared by coating PANI–CNT hydrogels onto a printed electrode plate, which exhibited good sensitivity (254.54 μA mM −1 cm −2 ). These PANI–CNT hydrogels present giant potential in the designing of flexible and wearable sensors, in which the composite hydrogels can function both as a sensor and an electrolyte storage unit simultaneously.